Determining Tarsus Curvature in Relation To Direction of Gaze Using Non-contact Ultrasound Video Assistance - Schrom, T.; Amberg, R.; Bast, F. (Ultrasound International Open, 2016)
Plastic surgery on the eyelids for the purpose of aesthetic or functional correction requires precise knowledge of lid anatomy. Changes in the tarsal curvature of the upper eyelid relative to line of vision are important, particularly when a surgical correction of paralytic lagophthalmos is undertaken. We used a computer-based image-processing algorithm to establish a relationship between changes in the curvature of the tarsus relative to the line of vision.A dynamic, ultrasound examination of the upper eyelids of 100 participants (100 eyes) was performed transpalpebrally using a 7.5 MHz scanner with the patient looking straight ahead, away from and towards the midline of the body. A computer-aided examination of the upper eyelid tarsus was then performed, followed by the calculation of the radius of curvature of the tarsus relative to the line of vision in each position.Using regression of a Taylor polynomial, the shape of the tarsus was mapped by a quadratic function, and the change in tarsal curvature relative to line of sight could be demonstrated.With objective evidence of change in the tarsal curvature relative to the line of sight, this may influence the treatment of pathological changes in the upper eyelid.
Keywords: eye; face; ultrasound